A Proposal for Reliability Evaluation of Components on Electric Power Distribution System Integrating Probabilistic Models and Fuzzy Inference Systems - Piasson, D. [UNESP] (2012)
The system reliability depends on the reliability of its components itself. Therefore, it is necessary a methodology capable of inferring the state of functionality of these components to establish reliable indices of quality. Allocation models for maintenance and protective devices, among others, have been used in order to improve the quality and availability of services on electric power distribution systems. This paper proposes a methodology for assessing the reliability of distribution system components in an integrated way, using probabilistic models and fuzzy inference systems to infer about the operation probability of each component.